Potential mobilizable Fe from secondary phases of differentially altered subsurface basaltic rock– a sequential extraction study on ICDP site Hawaii. (October 2020) - Stranghoener, Marius; Dultz, Stefan; Behrens, Harald; Schippers, Axel
Abstract: The potential for the mobilization of Fe from secondary phases within subsurface basaltic rocks of the Hawaii Scientific Drilling Project Phase2 (HSDP2) drill core was investigated to elucidate the possible contribution of volcanic islands to the Fe budget of nearby ocean surface waters. Rock specific parameters governing Fe mobilization, such as Fe redox state, specific surface area (SSA), and connected porosity were determined. A four-step sequential extraction procedure using solutions with increasing strength of the extractants was applied to characterize different states of chemical bonding of Fe in secondary phases of the basaltic rocks, a controlling parameter for its release to oceanic water. The sequential extraction results were then used as a measure for the reactivity of secondary Fe-bearing phases and the mobilizable Fe from these rocks. Basaltic rocks with different degrees of weathering showed elevated Fe(III) contents up to 58% total Fe as Fe(III), compared to 11–18% in fresh basalts. SSAs increased with depth, with maximum values of 70 m 2 /g observed for hyaloclastites. Both parameters depended mainly on the alteration state of the basalt, which was more strongly affected by the fluid chemistry (freshwater ↔ seawater) than by the age of the rocks. The sequential extractions revealed the presence of highly reactive secondary Fe-bearing phases in submarine rocks exposed to seawater whereas observations for rocks altered in freshwater point to better crystallized phases with lower mobilizable Fe contents. In seawater, aging of secondary Fe-bearing phases was most probably suppressed by the adsorption of silica and multivalent anions. Comparing different types of rock, hyaloclastites and pillow basalts showed the highest mobilizable Fe with up to 19% and 16%, respectively, of the total Fe of the bulk rock. The potential for high amounts of mobilizable Fe from basaltic rocks altered under seawater dominated conditions suggests that the submarine part of volcanic ocean islands represent an underestimated source of Fe supply to ocean surface waters. Highlights: Chemical bonding of Fe in basaltic rocks was determined by a four-step sequential extraction procedure. Highly reactive secondary Fe-bearing phases were present in submarine rocks exposed to seawater. Aging of secondary Fe-bearing phases in seawater was probably suppressed by anion adsorption. Hyaloclastites and pillow basalts showed highest mobilizable Fe strongly depending on specific surface area. The submarine part of volcanic islands is an underestimated source for Fe supply to ocean surface waters.